In vitro clearance of dexmedetomidine in extracorporeal membrane oxygenation. (January 2013) - Wagner, D; Pasko, D; Phillips, K; Waldvogel, J; Annich, G
Dexmedetomidine (DMET) is a useful agent for sedation, both alone and in combination with other agents, in critically ill patients, including those on extracorporeal membrane oxygenation (ECMO) therapy. The drug is a clonidine-like derivative with an 8-fold greater specificity for the alpha 2-receptor while maintaining respiratory and cardiovascular stability. An in vitro ECMO circuit was used to study the effects of both "new" and "old" membrane oxygenators on the clearance of dexmedetomidine over the course of 24 hours. Once primed, the circuit was dosed with 840 μg of dexmedetomidine for a final concentration of 0.9 μg/ml. Serial samples, both pre- and post-oxygenator, were taken at 5, 60, 360, and 1440 minutes. Concentrations of the drug were expressed as a percentage of the original concentration remaining at each time point, both for new and old circuits. The new circuits were run at a standard flow for 24 hours, after which time the circuit was considered old and re-dosed with dexmedetomidine and the trial repeated. Results show that dexmedetomidine losses occur early in the circuits and then continue to decline. Initial losses in the first hour were 11+-65% and 59-73% pre- and post-oxygenator in the new circuit and 36-50% and 42-72% in the old circuit. The clearance of the drug through the membrane oxygenator exhibits no statistical difference between pre and post or new and old circuits. Dexmedetomidine can be expected to exhibit concentration changes during ECMO therapy. This effect appears to be more related to adsorption to the polyvinyl chloride (PVC) tubing rather than the membrane oxygenator. Dosage adjustments during dexmedetomidine administration during ECMO therapy may be warranted in order to maintain adequate serum concentrations and, hence, the desired degree of sedation.*(Lack of equilibrium)